A soldier's soldier a biography of Lieutenant-General Sir Thomas Daly - Grey, Jeffrey (Australian Army history series., 2013)
Lieutenant-General Sir Thomas Daly was a renowned soldier and one of the most influential figures in Australia's military history. As Chief of the General staff during the Vietnam War, he oversaw a reorganisation of the Army. The author shows how Daly prepared himself for the challenges of command in a time of political upheaval.